Good Sleep Strategies to Prevent Hypertension in Teenagers - Susanti, Novi; Damayanti, Evi; Zakwan, M. Hadin; Octavia, Rizka (Universitas Ibn Khaldun Bogor, 2024)
In the context of preventing hypertension in adolescents, good sleep strategies such as maintaining a regular sleep schedule, creating a comfortable sleeping environment, and reducing the use of electronic devices before bed also need to be considered. Lack of quality sleep can interfere with nervous system function and increase blood pressure, so it's important for teens to prioritize getting enough sleep. This study aims to outline the importance of good sleep as a hypertension prevention strategy in adolescents. By understanding the relationship between sleep and hypertension and implementing effective sleep strategies. The research method used in writing this article is a literature study, which is a systematic approach to review, analyze, and synthesize various sources of information relevant to the research topic, namely good sleep strategies to prevent hypertension in adolescents. The results of the study show that adequate and quality sleep plays an important role in preventing hypertension in adolescents. Effective sleep strategies, such as maintaining a regular sleep schedule and creating a comfortable sleeping environment, can help lower the risk of high blood pressure in adolescents. Therefore, awareness of the importance of good sleep should be increased as an integral part of adolescent health programs.